Calcium antagonists in hypertension: relation to abnormal sodium transport. Issue 6403 (12th November 1983) - Heagerty, A M; Bing, R F; Thurston, H; Swales, J D
Abstract : Leucocyte sodium efflux rate constants and intracellular electrolyte contents were estimated in 13 patients with untreated essential hypertension. There was no correlation between intracellular sodium or potassium content or efflux rate constant and blood pressure. The patients were then treated with oral nifedipine and blood pressure controlled. Sodium efflux rate constants and electrolyte contents were estimated one and three months after the start of treatment. There was a significant fall in blood pressure, but mean sodium efflux rate constant and intracellular sodium content were unchanged. There was no correlation between the fall in blood pressure, initial sodium efflux, or intracellular sodium content. These data do not support the hypothesis that the sodium pump and intracellular sodium content have a direct role in generating raised blood pressure, or that treatment of hypertension with calcium antagonists corrects a fundamental alteration of calcium-sodium exchange across the cell membrane.